Characterization and quantitation of the polyphenolic compounds detected in methanol extracts of Pistacia atlantica Desf. fruits from the Guelmim region of Morocco - Khallouki, Farid; Breuer, Andrea; Ulrich, Cornelia; Owen, Robert (Journal of pharmaceutical and biomedical analysis, 2017)
High performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC-ESI-MS) was used for the identification of the major phenolic compounds in mature P. atlantica fruits from the Guelmim region (southeast of Morocco). In this study twenty seven polyphenolic compounds are identified and quantitated. To date, this is the most comprehensive report on the polyphenolic content of Pistacia fruits. The profiles comprise, three major polyphenolic classes, namely gallates (18.76g/kg; 63.92%), flavonoids (10.12g/kg; 34.48%) and ellagic acid derivatives (0.47g/kg; 1.60%) with a total of 29.35g/kg detected. The major gallate was pentagalloyl glucoside (5.0g/kg; 17.04% of total polyphenolics), the major flavonoid luteolin (3.18g/kg; 10.83% of total polyphenolics) and the major ellagic acid derivative ellagic acid (0.25g/kg; 0.85% of total polyphenolics). Identification of galloyl quinate, digalloyl quinates (x 2), galloyl glucoside, digalloyl glucosides (x 2), trigalloyl glucoside, tetragalloyl glucosides (x 2), pentagalloyl glucoside, 2″-O-galloyl-quercetin-3-O-galactoside, quercetin-3-O-rhamnogalactoside, quercetin-3-O-galactoside, ellagic acid diglucoside, luteolin-4′-O-glucoside, 2″-O-galloyl-luteolin-4′-O-glucoside, quercetin-3-O-glucuronide, kaempferol-3-O-glucoside, eriodictyol, apigenin, ellagic acid diglucoside, ellagic acid glucoside, methyl ellagic acid glucoside, and ellagic acid are described as phytochemical components of Pistacia fruits for the first time.